Balloon pressure monitoring for radial artery hemostasis after transradial coronary procedures: protocol for a randomized controlled trial - Xiaodong Zhang; Lan Zou; Dunfu Zhang; Bangtao Yao; Junge Chen; Tianfeng Wei; Zhouping Fu; Xin Chang; Lijuan Chen; Yan Geng (PLoS ONE, 2026)
Background Forearm radial artery occlusion (RAO) is a common complication after transradial coronary procedures. Traditional patent hemostasis, relying on operator-dependent assessment, results in labor-intensive processes and inconsistent RAO rates. Methods This is a single-center, prospective, randomized, open-label, parallel-group superiority trial. We plan to enroll 818 patients scheduled for transradial coronary angiography. Participants will be randomly assigned (1:1) to either a novel balloon pressure monitoring system (integrating high-precision digital manometry with physiologically-phased decompression) or traditional patent hemostasis. The primary outcome is the incidence of ultrasound-confirmed forearm RAO at 24 hours post-procedure. Key secondary outcomes include rates of access-site vascular complications and bleeding events, as well as objective metrics of hemostasis efficiency. Recruitment Status: Recruitment commenced in September 2024 and is ongoing; the target sample size is anticipated to be reached by May 2026. Analysis will follow the intention-to-treat principle. Results/ Trial Status As a protocol paper, no results are reported. The trial is currently in the recruitment phase. Conclusions This trial will provide the first large-scale randomized evidence on whether digital manometry-guided compression reduces RAO, potentially bridging the efficacy-effectiveness gap between optimized research protocols and routine practice. Trial registration The trial was registered with the Chinese Clinical Trial Registry (ChiCTR) in August 2024, under the registration number ChiCTR2400088258.